2022
DOI: 10.1002/eom2.12208
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic three‐dimensional hollow nanoporous CuxO encapsulated mesoporous Cu heterostructures with superior Li storage properties

Abstract: Drastic volume expansion and low conductivity are critical factors leading to severe capacity decay of transition metal oxides (TMOs) as anodes for lithium‐ion batteries (LIBs). An effective strategy to overcome this challenge is to engineer freestanding 3D hollow architectures integrated with nanostructured metals to boost their structural stability and electrical conductivity simultaneously. Inspired by cowpea configuration beneficial to improve the transport of rich water in arid environment, herein, a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…Also, the other two peaks are associated with the bonds of Si–Si (99.79 eV) and Si–C (102.48 eV). In Figure e, a set of fitted peaks match the C–O, Si–O, and CO bonds (530.84, 532.76, and 533.04 eV), respectively. ,,, The peaks in the D (1366 cm –1 ) and G (1594 cm –1 ) bands in the Raman spectrum of N-C@m-HNP Si (Figure f) correspond to disordered carbon and graphitic carbon, respectively. The intensity ratio between peaks D and G ( I D / I G ) indicates the degree of graphitization of the carbon. , The higher the I D / I G value, the more disordered the carbon is and the poorer the crystallinity. The I D / I G of the carbon layer formed by polydopamine carbonization is 0.851, indicating that it has a significant degree of disorder.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, the other two peaks are associated with the bonds of Si–Si (99.79 eV) and Si–C (102.48 eV). In Figure e, a set of fitted peaks match the C–O, Si–O, and CO bonds (530.84, 532.76, and 533.04 eV), respectively. ,,, The peaks in the D (1366 cm –1 ) and G (1594 cm –1 ) bands in the Raman spectrum of N-C@m-HNP Si (Figure f) correspond to disordered carbon and graphitic carbon, respectively. The intensity ratio between peaks D and G ( I D / I G ) indicates the degree of graphitization of the carbon. , The higher the I D / I G value, the more disordered the carbon is and the poorer the crystallinity. The I D / I G of the carbon layer formed by polydopamine carbonization is 0.851, indicating that it has a significant degree of disorder.…”
Section: Resultsmentioning
confidence: 97%
“…Silicon (Si) is considered a promising candidate for anodes in lithium-ion batteries due to its high theoretical specific capacity (3579 mAh g –1 ) at room temperature and abundant natural resources . However, Si anodes undergo a significant volume change (∼300%) during the lithiation/delithiation process, leading to internal stress and various problems with active substance falling off the collector, instability of the solid electrolyte interface (SEI) layer, failure of the electrical connection between the active substance and the collector, and a decrease in battery capacity, conductivity, and cycle life. To address these issues, many excellent studies have been reported, including the preparation of Si nanoparticles, , nanorods, nanowires, and nanotubes, the development of active-inertia systems, and the construction of porous structures. , Among these, reducing the particle size can stabilize the performance of Si anodes, but significant internal stress accumulates during multiple charges and discharges, eventually leading to battery failure. In contrast, the construction of porous structures can better stabilize the performance of Si anodes. For example, Sohn et al prepared nonporous and porous micrometer-sized Si/C composite anodes by ball milling and alkaline etching .…”
Section: Introductionmentioning
confidence: 99%
“…prepared the heterogeneous structure 3D‐HNP‐Cu x O@m‐Cu by a simple three‐step method. [ 114 ] In the long cycle performance test, it can be seen that 3D‐HNP showed excellent electrochemical performance, and the battery capacity did not show substantial decline during the 200 cycles of charging and discharging. Core‐shell structure as the control group 3D‐NPCS‐CuxO@m‐Cu showed poor performance ( Figure ).…”
Section: Multiple Structural Models For Stress Reliefmentioning
confidence: 99%
“…Reproduced with permission. [ 114 ] Copyright 2022, Wiley. b) Synthesis of layered VS 2 /MoS 2 heterostructures.…”
Section: Multiple Structural Models For Stress Reliefmentioning
confidence: 99%
See 1 more Smart Citation